THE INFLUENCE OF PAPEA (NUMBER ADVENTURE BOARD) MEDIA ON MATHEMATICS LEARNING OUTCOMES OF THIRD-GRADE ELEMENTARY STUDENTS - Sinaga, Ruth Silvia; Dinita, Daniar Rahmah; Rozi, Fahrur; Ellianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examined the effect of Papea (Papan Petualangan Angka) on third-grade students’ mathematics learning outcomes, particularly in understanding whole numbers and place value. Using a one-group posttest-only quasi-experimental design with 42 participants, the study found that the use of Papea significantly improved students’ performance, as reflected by the increase in the mean score from 40.79 to 78.95 and the paired-sample t-test result of t = –10.50 (p = 1.20 × 10⁻¹²). These findings indicate that Papea effectively enhances students’ comprehension of numerical concepts, supports more accurate problem solving, and increases engagement during learning activities.